Geological risks in large cities: the landslides triggered in the city of Rome (Italy) by the rainfall of 31 january-2 february 2014 - Alessi, Dario; Bozzano, Francesca; Di Lisa, Andrea; Esposito, Carlo; Fantini, Andrea; Loffredo, Adriano; Martino, Salvatore; Mele, Francesco; Moretto, Serena; Noviello, Alessandra; Prestininzi, Alberto; Sarandrea, Paolo; et al. (Italian journal of engineering geology and environment, 2014)
An exceptional rainfall battered the city of Rome (Italy) from 31 January to 2 February 2014. The event had variable intensity and duration in the different parts of the city. The exceptionality of the event lies in the intensity of rainfall cumulated in 6 hours (return period > 50 years) and in its uneven distribution over the urban area. The event triggered a number of landslides of different type, which caused substantial damage. researchers from the Centro di Ricerca per i Rischi Geologici (research centre on prediction, prevention and control of geological risks - cEri) of the university of Rome “Sapienza” carried out field surveys and assessments immediately after the event. The team detected and inventoried 68 landslides, mostly occurring in the sandy and sandy-silty deposits of the Monte Mario, Ponte Galeria and Valle Giulia Formations. The complete inventory of the landslides is accessible via WebGIS on CERI’s website http://www.ceri. uniroma1.it/cn/landslidesroma.jsp. The spatial distribution of the landslides evidences that 69% occurred in clastic deposits of sedimentary origin and only 6% in volcanic deposits. this finding disagrees with more general statistical data, based on the inventory of rome’s historical landslides, indicating that almost 41% of slope instabilities occur in volcanic deposits and almost 12% in sedimentary ones. in the data reported here, this apparent contradiction is justified by the fact that most the rainfall under review was concentrated in the north-western portion of rome’s urban area, whose hills accommodate outcrops of dominantly sedimentary deposits from plio-pleistocene marine and continental cycles.